Program Pencegahan Stunting Melalui Sosialisai Pola Hidup Sehat di Kabupaten Kutai Timur - Satriah, Satriah; Prima, Anggra (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
Reducing stunting and sanitation have become important goals in national sustainable development. Nutrition and sanitation education are very important to prevent stunting because children's growth and development require optimal nutrition and a healthy environment. This research is a community service activity formulated in the form of socialization of stunting prevention and reduction in East Kutai Regency. This activity aims to provide students with an understanding of the need for early stunting prevention and can play a role in improving adolescent nutrition, especially iron in adolescents as preparation for becoming prospective mothers to prevent anemia. Furthermore, it can be concluded that Stunting is a world problem because its implications determine the future of the nation. Indonesia as a developing country has a high prevalence of stunting, so various prevention efforts are needed, including through socialization as carried out at the Sangatta Kutai Timur Islamic College